Gate-Tunable and Multidirection-Switchable Memristive Phenomena in a Van Der Waals Ferroelectric - Xue, Fei (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.